PENGARUH PERLAKUAN ALKALI TERHADAP SIFAT FISIS DAN MEKANIS SERAT LANTUNG (ARTOCARPUS ELASTICUS) - Hendri Hestiawan; Dody Ariawan; Khairul Amri; Agus Nuramal; Aditya Afrizal; Sudibyo Sudibyo (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
Alkali treatment of natural fibers is one of the chemical treatments used to increase the exposed cellulose content through the removal of hemicellulose and lignin on the fiber surface. This study aims to investigate the effect of alkali treatment on the physical and mechanical properties of lantung fibers. The materials used in this research consist of: lantung fiber (Artocarpus elasticus) with an alkali treatment process using 4% and 6% natrium hydroxide (NaOH) solutions and immersion time of 1 and 2 hours, at room temperature. The fiber neutralization process includes washing the fibers using fresh water and drying them at room temperature for 48 hours. Tests carried out include XRD test, SEM photo observations conducted at Balai Penelitian Teknologi Mineral, Lembaga Ilmu Pengetahuan Indonesia and fiber tensile test based on ASTM D 3379 standard. The results of XRD and fiber tensile test showed that alkali treated lantung fibers were effective in increasing the crystallization index (CI) value and fiber tensile strength. The highest CI values and fiber tensile strength were obtained at alkali treatment of 4% NaOH for 2 hours, respectively 85.42% and 228.5 MPa. The results of SEM photo observations showed that alkali treatment on the fiber surface could remove impurities based on the concentration of sodium hydroxide (NaOH) solution and soaking time. This shows that proper alkali treatment can increase the strength of lantung fibers.